Elevated Serum Amyloid A Is Associated With Cognitive Impairment in Ischemic Stroke Patients - Zhang, Yun; Feng, Yue; Zuo, Jiacai; Shi, Jian; Zhang, Shanshan; Yang, Yao; Xie, Shu; Chen, Zhonglun (Frontiers in Neurology, 2022)
Background and Purpose. The impact of serum amyloid A (SAA) on cognitive impairment after ischemic stroke is unclear. We aimed to investigate the association between SAA levels and post-stroke cognitive impairment (PSCI) at 3 months after ischemic stroke. Methods. One hundred and ninety-eight patients were enrolled prospectively from June 2020 to April 2021. The SAA concentrations were measured using a commercially available enzyme-linked immunosorbent assay kit after admission. Cognitive function was assessed using the Montreal Cognitive Assessment score at 3 months after symptoms onset. We defined a Montreal Cognitive Assessment score <25 as cognitive impairment. Results. During 3-month follow-up, 80 patients (40.4%) were diagnosed as having PSCI. As compared with cognitively normal ischemic stroke patients, those with PSCI were older, and more likely to have diabetes and white matter lesions, and had higher baseline National Institutes of Health stroke score and SAA levels. After adjustment for age, National Institutes of Health stroke score and other covariates, the odds ratio for the highest quartile of SAA compared with the lowest quartile was 5.72 (95% confidence interval, 2.17–15.04, P = 0.001) for PSCI. Also, ordinal logistic regression analysis showed that higher SAA concentrations were associated with increased risk of PSCI severity (odds ratio, 4.31; 95% confidence interval, 1.81–10.33, P = 0.001). Similar results were found when the SAA levels were analyzed as continuous variable. Conclusions This present study demonstrated that increased SAA levels might be associated with PSCI at 3 months after ischemic stroke.